Makoons ebook - Erdrich, Louise (The Birchbark House, 2016)
In this award-winning sequel to Chickadee, acclaimed author Louise Erdrich continues her celebrated Birchbark House series with the story of an Ojibwe family in nineteenth-century America. Named for the Ojibwe word for little bear, Makoons and his twin, Chickadee, have traveled with their family to the Great Plains of Dakota Territory. There they must learn to become buffalo hunters and once again help their people make a home in a new land. But Makoons has had a vision that foretells great challenges—challenges that his family may not be able to overcome. Based on Louise Erdrich's own family history, this fifth book in the series features black-and-white interior illustrations, a note from the author about her research, and a map and glossary of Ojibwe terms.